Identifikasi Faktor Yang Mempengaruhi Kemiskinan Di Provinsi Bengkulu - Mintargo Mintargo; Barika Barika; Edy Rahmantyo (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2018)
The purpose of this research is to analyze the effect of unemployment with skill (X1), amount of population (X2), and minimum of wage region (X3) against proverty (Y) in Bengkulu Province. The method of analysis by an Ordinary Least Square (OLS). The data that used in this research is pooled data from BPS (Badan Pusat Statistik) of Bengkulu Province and Bapenas (period of data is 2009 – 2013 ). From the output of regression with Eviews (econometric views) aplication indicated that amount of population (X2) having significant effect against proverty (Y). unemployment with skill (X1) is not significant with proverty (Y), and the last minimum of wage region (X3) isnot significant too with proverty (Y). The coefisien regression of variables are coefisien regress of X1 aqual -0.0001200, coefisien regress of X2 equal 0.000200, and coefisien regress of X3 equal -5.18E-06.